Acoustic and optical phonons in metallic diamond - M. Hoesch, T. Fukuda, T. Takenouchi, J.P. Sutter, S. Tsutsui, A.Q.R. Baron, M. Nagao, Y. Takano, H. Kawarada and J. Mizuki (Science and Technology of Advanced Materials, 2006)
The dispersion of acoustic and optical phonons in highly boron-doped diamond has been measured by inelastic X-ray scattering at an energy resolution of 6.4 meV. The sample is doped in the metallic regime and shows superconductivity below 4.2 K (midpoint). The data are compared to pure and nitrogen-doped diamond that represent the non-metallic state. No difference is found for the acoustic phonons in the three samples, while the optical phonons show a shift of the dispersion (softening) in qualitative agreement with earlier results from Raman spectroscopy. The presence of boron and nitrogen incorporated into the diamond lattice leads to structural disorder. Evidence for this is found both in the observation of otherwise symmetry-forbidded Bragg intensity at (0 0 2) and intensity from acoustic phonon modes in the vicinity of (0 0 2).